A new technique for recovering aged mineral oil to promote lifetime and sustainability - Sarathkumar, D.; Montanari, Gian Carlo; Sarathi, R.; Srinivasan, M.; Karthik, R.; Sivadasan, J. (Frontiers in Materials, 2023)
The use of mineral oil (MO) derived from petroleum for, e.g. transformer insulation, raise environmental risk and affect sustainability. Due to its affordability and easy availability, MO will ineluctably be preferred over other biodegradable oils. Therefore, tools to recover aged MO, extending life cycle and increasing its sustainability must be developed. The work presented here is aimed at the investigation of the electrical insulation properties of thermally-aged recovered-aged mineral oil (RAMO), as well as of aged cellulose pressboard impregnated by fresh mineral oil (FMO), aged mineral oil (AMO), and RAMO. The AMO is recovered using the combined adsorbents, A* and B*, which are Chitosan-activated Bentonite (CTN-aB) and Polyaniline coated Kapok Fiber (PANI-c-KPF) mix. According to FTIR, the recovered oil, RAMO, displays less C=C double bonds and carbonyl vibrations at 140°C, which is an indication of lower oil aging compared to AMO. The distribution of the crystalline and amorphous peaks is uniform for aged oil impregnated pressboard (PB) with FMO and RAMO. Overall, it has been discovered that PB impregnated with RAMO resulting in an extended lifetime for the solid insulation. As a result, the rate of increase in emissions slows down, and global sustainability targets are met.